A highly effective reverse-transcription loop-mediated isothermal amplification (RT-LAMP) assay for the rapid detection of SARS-CoV-2 infection. Issue 1 (January 2021) - Fowler, Veronica L.; Armson, Bryony; Gonzales, Jose L.; Wise, Emma L.; Howson, Emma L.A.; Vincent-Mistiaen, Zoe; Fouch, Sarah; Maltby, Connor J.; Grippon, Seden; Munro, Simon; Jones, Lisa; Holmes, Tom; et al.
Highlights: Novel rapid RT-LAMP assay with diagnostic sensitivity and specificity of 97% and 99%. Development of an RNA extraction free direct detection method for SARS-CoV-2. Use case modelling for rapid direct RT-LAMP in near-patient clinical practice. Developing diversity of testing modalities within a diagnostic laboratory during a pandemic. Summary: The COVID-19 pandemic has illustrated the importance of simple, rapid and accurate diagnostic testing. This study describes the validation of a new rapid SARS-CoV-2 RT-LAMP assay for use on extracted RNA or directly from swab offering an alternative diagnostic pathway that does not rely on traditional reagents that are often in short supply during a pandemic. Analytical specificity (ASp) of this new RT-LAMP assay was 100% and analytical sensitivity (ASe) was between 1 × 10 1 and 1 × 10 2 copies per reaction when using a synthetic DNA target. The overall diagnostic sensitivity (DSe) and specificity (DSp) of RNA RT-LAMP was 97% and 99% respectively, relative to the standard of care rRT-PCR. When a CT cut-off of 33 was employed, above which increasingly evidence suggests there is a low risk of patients shedding infectious virus, the diagnostic sensitivity was 100%. The DSe and DSp of Direct RT-LAMP (that does not require RNA extraction) was 67% and 97%, respectively. When setting CT cut-offs of ≤33 and ≤25, the DSe increased to 75% and 100%, respectively, time from swab-to-result, CT < 25, was < 15 min. We propose that RNA RT-LAMP could replace rRT-PCR where there is a need for increased sample throughput and Direct RT-LAMP as a near-patient screening tool to rapidly identify highly contagious individuals within emergency departments and care homes during times of increased disease prevalence ensuring negative results still get laboratory confirmation.